2011
DOI: 10.1111/j.1559-1816.2011.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Studying Ideological Groups Online: Identification and Assessment of Risk Factors for Violence

Abstract: Recent acts of violence have demonstrated the impact of violent ideological groups worldwide. However, the systematic study of these groups is somewhat limited. The Internet is a valuable tool for investigating ideological group behavior because it is easily accessible and commonly used by these groups. This study attempted to extend previous research by examining online message boards to assess processes particular to ideological group membership. A content analysis was conducted on several group process vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 50 publications
1
18
0
2
Order By: Relevance
“…Despite evidence that both conservatives and liberals hold similar negative perspectives of each other, it is unclear whether extreme conservative messages influence message receivers in the same way as extreme liberal messages. Previous research has generally limited classification of ideological groups to violent or non-violent (Angie et al, 2011) or explored the reactions to only one extreme ideological message (G. Johnson et al, 2014). Additionally, although some research has been conducted investigating the components of ideological messages, which research provides important insight into the persuasive goals and tactics of extreme ideological groups, this research tends to be qualitative or ethnographic in nature (Angie et al, 2011), which limits the generalizability of the findings.…”
Section: Online Ideological Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite evidence that both conservatives and liberals hold similar negative perspectives of each other, it is unclear whether extreme conservative messages influence message receivers in the same way as extreme liberal messages. Previous research has generally limited classification of ideological groups to violent or non-violent (Angie et al, 2011) or explored the reactions to only one extreme ideological message (G. Johnson et al, 2014). Additionally, although some research has been conducted investigating the components of ideological messages, which research provides important insight into the persuasive goals and tactics of extreme ideological groups, this research tends to be qualitative or ethnographic in nature (Angie et al, 2011), which limits the generalizability of the findings.…”
Section: Online Ideological Groupsmentioning
confidence: 99%
“…Previous research has generally limited classification of ideological groups to violent or non-violent (Angie et al, 2011) or explored the reactions to only one extreme ideological message (G. Johnson et al, 2014). Additionally, although some research has been conducted investigating the components of ideological messages, which research provides important insight into the persuasive goals and tactics of extreme ideological groups, this research tends to be qualitative or ethnographic in nature (Angie et al, 2011), which limits the generalizability of the findings. For example, recent research has looked at credibility and persuasive features present on ideological websites , social identity processes used (Connelly et al, 2015) and the use of social media .…”
Section: Online Ideological Groupsmentioning
confidence: 99%
“…A majority of individuals living in the United States claim membership in some sort of ideological group, including those who promote religious, political, professional, or community-focused ideologies (U. S. Census Bureau, 2012;Van Dijk, 2006). Despite the large variety of ideological groups represented online, previous research has generally treated all ideological groups the same or presented limited classifications to describe a vibrant and diverse sector of society (Angie et al, 2011). More recent research has attempted to take a more nuanced view of online ideological groups by investigating credibility and persuasive features of ideological websites , interactivity of ideological group websites , how conservative versus liberal ideologies of groups influence people's perceptions of credibility , and how ideological groups construct and differentiate their identities online .…”
Section: Ideological Groupsmentioning
confidence: 98%
“…Violence may even be an integral part of the system of ideological beliefs (Moghaddam, ). In general, violent ideological groups are defined as groups of individuals united by a specific set of values that either openly condone violence or have been linked to multiple acts of violence (Angie, et al, ). These groups also tend to be identified by their alignment with an extremist ideology that is used to justify the aggressive acts they pursue.…”
Section: Elaboration Likelihood Modelmentioning
confidence: 99%
“…For example, using thematic content analysis, McNamee, Peterson, and Peña () identified four types of goals common across a variety of hate groups. Angie et al () revealed a number of differences in the psychological processes used by ideological groups that sanction violence compared to ideological groups that do not, while Byrne et al () contrasted various website characteristics for violent and nonviolent ideological groups. However, much more research is needed to improve our understanding of the advocacy used in these messages.…”
mentioning
confidence: 99%